2008
DOI: 10.1007/s00281-008-0105-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunological mechanisms in glaucoma

Abstract: Glaucoma is one of the most frequent causes of blindness worldwide. The elevated intraocular pressure does not explain glaucoma in all patients but can be considered as a risk factor of the disease. There are some evidences that autoimmune mechanisms may be involved in this disorder. This review attempts to demonstrate the findings about autoimmune mechanisms in glaucoma patients. Consistent up- and down-regulations in the autoantibody profiles against ocular antigens are present in glaucoma patients. These ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
0
12
0
1
Order By: Relevance
“…815,43,44,4954 Given that an increase in the reactivity associated with specific autoantibodies can exist in humans with other autoimmune diseases for extended periods prior to onset of symptoms, this information may be useful in developing screening tools and treatments for glaucoma. 3,5557 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…815,43,44,4954 Given that an increase in the reactivity associated with specific autoantibodies can exist in humans with other autoimmune diseases for extended periods prior to onset of symptoms, this information may be useful in developing screening tools and treatments for glaucoma. 3,5557 …”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune responses generated in response to insults can in some situations be protective or play a role in reestablishing homeostasis, sometimes via pathways other than typical antigen-antibody interactions. 3,58,59 Several studies have been performed to evaluate broader patterns of serum and aqueous humor autoantibodies against retinal and optic nerve antigens in glaucomatous humans with digests of those tissues as antigen sources. In people, serum and aqueous humor autoantibody patterns differ significantly between individuals with and without glaucoma and across various categories of disease, including primary open-angle glaucoma, normal-tension glaucoma, and ocular hypertension without glaucoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from numerous studies support the notion that both the innate and adaptive immune responses are involved in the pathogenesis of glaucoma. 1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Yet, the precise mechanisms of immune responses and the specific cell interactions contributing to the disease process are still not fully understood. Many questions remain about the role of the immune system in glaucoma ( Figure 1).…”
Section: The Immune System Has Been Implicated In the Pathogenesis Ofmentioning
confidence: 99%
“…1,2,17,18 Studies have shown the presence of autoantibodies against ocular antigens such a rhodopsin and glycosaminoglycans (GAGs). 1,7,[38][39][40] It has been revealed that patients with normal tension glaucoma have increased levels of heat shock proteins, such as heat shock protein 60 (HSP 60), due to excessive tissue stress and damage. 17,18,[41][42][43] But there is no direct evidence to confirm that RGC loss is due to humoral immunity in glaucoma.…”
Section: Autoimmunity and Glaucomamentioning
confidence: 99%